2012 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2012
DOI: 10.1109/embc.2012.6346173
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility study of an upper limb rehabilitation system using kinect and computer games

Abstract: A new low-cost system for rehabilitation of the impaired upper limb for stroke survivors is presented. A computer game was developed specifically for this purpose and the user's impaired upper extremity is tracked using a downward-pointed Kinect, an inexpensive motion capture system commercially available from Microsoft. A Kalman filter was implemented to reduce data jittering. Patients are required to move their impaired arm, sliding it on top of a transparent support, in order to play the game. The game is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
77
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 11 publications
0
77
0
1
Order By: Relevance
“…Several studies have compared the Kinect-based and motion tracking system-based posture and movement, in various fields of biomechanics including; anthropometry measurement (Bonnech ere et al, 2014), spinal loading assessment (Ning and Guo, 2013), clinical foot posture assessment (Mentiplay et al, 2013), body movement during postural control (Clark et al, 2012), gait training (Clark et al, 2013b), gait analysis (Clark et al, 2013a), and rehabilitation tool development (Pastor et al, 2012). In general, the results of these studies indicated that, although the Kinect sensor is not as accurate as more traditional laboratory-based measurement technologies, it does provide good agreement with a motion tracking system in terms of body segment lengths, the major joint angles, and the displacement of the key body joints for those specific body postures being tested.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have compared the Kinect-based and motion tracking system-based posture and movement, in various fields of biomechanics including; anthropometry measurement (Bonnech ere et al, 2014), spinal loading assessment (Ning and Guo, 2013), clinical foot posture assessment (Mentiplay et al, 2013), body movement during postural control (Clark et al, 2012), gait training (Clark et al, 2013b), gait analysis (Clark et al, 2013a), and rehabilitation tool development (Pastor et al, 2012). In general, the results of these studies indicated that, although the Kinect sensor is not as accurate as more traditional laboratory-based measurement technologies, it does provide good agreement with a motion tracking system in terms of body segment lengths, the major joint angles, and the displacement of the key body joints for those specific body postures being tested.…”
Section: Introductionmentioning
confidence: 99%
“…In one game, the user has to control an avatar in order to climb a hill, and on the other, control an avatar to run. For stroke rehabilitation as well, reference [14] presents a game for upper limbs rehabilitation, in which the Kinect sensor is mounted facing down, so it can measure the range of motion and speed of movement of the user's arms.…”
Section: Kinect For Xboxmentioning
confidence: 99%
“…This is an important feature because different studies proved that a deep involvement of the patients during the rehabilitation process leads to a better and faster recovery [13]. The main disadvantage of VEs is that often no feedback is provided to the patients: the goal of the game can often be reached using different strategies, such as for example compensation movements, that are not corrected by the system as would be by a real therapist [14].…”
Section: Introductionmentioning
confidence: 99%